2019
DOI: 10.1093/mnras/stz1207
|View full text |Cite
|
Sign up to set email alerts
|

Robust statistics towards detection of the 21 cm signal from the Epoch of Reionization

Abstract: We explore methods for robust estimation of the 21 cm signal from the Epoch of Reionisation (EoR). A Kernel Density Estimator (KDE) is introduced for measuring the spatial temperature fluctuation power spectrum from the EoR. The KDE estimates the underlying probability distribution function of fluctuations as a function of spatial scale, and contains different systematic biases and errors to the typical approach to estimating the fluctuation power spectrum. Extraction of histograms of visibilities allows momen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…True to its broad science case, the tile layout of the MWA is a hybrid between a spread out non-regular configuration and two closely packed, hexagonal grids of 36 tiles each [215]. The MWA has published a number of upper limits over a broad range of redshifts in recent years ranging from Cosmic Dawn redshifts to reionization redshifts [216][217][218][219][220][221][222][223][224].…”
Section: Eor Interferometersmentioning
confidence: 99%
“…True to its broad science case, the tile layout of the MWA is a hybrid between a spread out non-regular configuration and two closely packed, hexagonal grids of 36 tiles each [215]. The MWA has published a number of upper limits over a broad range of redshifts in recent years ranging from Cosmic Dawn redshifts to reionization redshifts [216][217][218][219][220][221][222][223][224].…”
Section: Eor Interferometersmentioning
confidence: 99%
“…This is useful when we want to reconstruct a distribution without making many assumptions about the data, as is required in parametric methods. KDEs have found use in many areas of astrophyics, for example to measure the 21cm power spectrum with reduced foreground contamination (Trott et al 2019), and to estimate luminosity functions with superior performance compared to binned methods (Yuan et al 2020). Hatfield et al (2016) uses a KDE approach to estimate the angular correlation function, in order to address the issues of information loss and arbitrary bin choice inherent to binning; they optimize for the kernel choice, and find a correlation function consistant with that of the binned method.…”
Section: Relationship To Other Modifications Of 2pcf Estimatorsmentioning
confidence: 99%
“…Beyond new analyses the extract cosmological information, the large systematic impediments presented currently by foreground signals demands careful attention. In [15], the EoR group used a kernel density estimator to study the distribution of data in different wavemodes from two different observing fields. This work showed that foregrounds differed between locations on the sky, potentially offering an avenue for future use of such estimators to discriminate isotropic cosmological signal from local foreground contamination.…”
Section: Pos(kmi2019)018mentioning
confidence: 99%